Levantamiento de información agrológica de suelos dedicados a la producción agrícola en la parroquia el cambio provincia de El Oro - Gomez Egas, Daniel Andres (2015)
The research of this work is for the purpose of obtaining detailed information of soils studied, using methodologies for the morphological study in the parish belongs to the canton of Machala, province of El Oro El Cambio. This work is conducted with the purpose of helping farmers with the knowledge of the potential that the soils has in the area and to know that crops are suitable for producing or proper management that should be given to these soils. For which held the morphological characterization and taxonomic classification of eight representative profiles of agricultural activity in the parish El Cambio. This research was conducted in Pajonal, La Iberia, Santa Inés, and La Union of the Canton Machala. The taxonomic description of the selected soils, is continued under the guidelines of the National Soil Survey Center (USDA) and the Guide for the description of soils (FAO). In physical and chemical characterization made in the laboratory of the Technical University of Machala, academic unit of agricultural sciences soil. The area identified with soils that are nearly homogeneous taxonomic and morphological properties. We found Entisols and Inceptisols of unconsolidated sedimentary origin, generated by frequent deposits of river character. Studied profiles, made it possible to characterize the most representative of the selected sectors edaphic conditions, giving way to the continuity of the study, which will be more representative with the increase in the number of assessments.